Formose reaction controlled by boronic acid compounds - Imai, Toru; Michitaka, Tomohiro; Hashidzume, Akihito (Beilstein Journal of Organic Chemistry, 2016)
Formose reactions were carried out in the presence of low molecular weight and macromolecular boronic acid compounds, i.e., sodium phenylboronate (SPB) and a copolymer of sodium 4-vinylphenylboronate with sodium 4-styrenesulfonate (pVPB/NaSS), respectively. The boronic acid compounds provided different selectivities; sugars of a small carbon number were formed favorably in the presence of SPB, whereas sugar alcohols of a larger carbon number were formed preferably in the presence of pVPB/NaSS.
Keywords: boronic acid compounds; formose reaction; sodium phenylboronate; sodium 4-vinylphenylboronate/sodium 4-styrenesulfonate copolymer; sugar alcohols; sugars